Social Empowerment of Uncapable Communities through Formal Education and Informal Education in Cirebon City - Sitti Faoziyah (International Journal of Science and Society, 2023)
This study aims to investigate the social empowerment of underprivileged and low-income communities through both formal and non-formal education in Cirebon City, West Java. The research method used is a literature study that focuses on the theme of Community Social Empowerment, formal and non-formal education. Resources come from secondary data in the form of public documents from the Office of Social Workers and Transmigration; Strategic Plan Document (RENSTRA) Cirebon City Education Office 2016-2021; and relevant literature. The results of the study consist of two sub-discussions. First, social empowerment of underprivileged communities through formal education is carried out in a simple and synergistic manner in accordance with the conditions of the community. Second, empowerment of low-income communities through non-formal channels is carried out through the concept of the Community Learning Activity Center (PKBM) and the Course & Training Institute (LKP). Both educational programs are said to be successful if there is a change for the better where the influence can be seen in the formation of characters such as self-confidence, creativity, and individual independence. The expected implication is that local governments can evaluate the Strategic Plan (RENSTRA) of the Cirebon City Education Office for 2016-2021 and carry out intense collaboration by collaborating with the private sector and educational institutions so that in the future, community social empowerment has a better contribution to national development. Both educational programs are said to be successful if there is a change for the better where the influence can be seen in the formation of characters such as self-confidence, creativity, and individual independence. The expected implication is that local governments can evaluate the Strategic Plan (RENSTRA) of the Cirebon City Education Office for 2016-2021 and carry out intense collaboration by collaborating with the private sector and educational institutions so that in the future, community social empowerment has a better contribution to national development. Both educational programs are said to be successful if there is a change for the better where the influence can be seen in the formation of characters such as self-confidence, creativity, and individual independence. The expected implication is that local governments can evaluate the Strategic Plan (RENSTRA) of the Cirebon City Education Office for 2016-2021 and carry out intense collaboration by collaborating with the private sector and educational institutions so that in the future, community social empowerment has a better contribution to national development.